Hypericin As A Possible Natural Molecule For The Treatment Of Alzheimer`s Disease: Computationa Studies Focused On Beta-Secretase-1(or BACE1) - Ferrari, van Vito (International Journal of Scientific Research in Biological Sciences, 2023)
In this short communication, for the first time computational approach through Molecular Docking by Autodock Vina was performed for the treatment of Alzheimer’s disease. In this investigation, hundreds of natural molecules were investigated by the Virtual Screening method with the Pyrx program using the Beta-Secretase-1 protein in the Ligand Binding Site protein. From docking results, Hypericin has obtained an excellent binding energy value of -10.6 kcal/mol rather than other compounds investigated. Several biological studies are needed both to demonstrate the role of Hypericin in its mechanism and toxicity studies to evaluate whether this molecule can actually be useful for the treatment of Alzheimer`s disease.